Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2013)
The first 2013 issue of Studies in Second Language Learning and Teaching brings together six contributions from scholars from different parts the world, five of which constitute reports of original research studies. As many as four of the papers are devoted to the role of affective factors in the process of learning and using second and foreign languages, which speaks to the considerable emphasis that is currently placed on the mediating effect of the affective domain.